Derivation and High Engraftment of Patient-Specific Cardiomyocyte Sheet Using Induced Pluripotent Stem Cells Generated From Adult Cardiac Fibroblast. (January 2015) - Zhang, Liying; Guo, Jing; Zhang, Pengyuan; Xiong, Qiang; Wu, Steven C.; Xia, Lily; Roy, Samit Sunny; Tolar, Jakub; O'Connell, Timothy D.; Kyba, Michael; Liao, Kenneth; Zhang, Jianyi
<x xml:space="preserve">Abstract</x> Background— Induced pluripotent stem cells (iPSCs) can be differentiated into potentially unlimited lineages of cell types for use in autologous cell therapy. However, the efficiency of the differentiation procedure and subsequent function of the iPSC-derived cells may be influenced by epigenetic factors that the iPSCs retain from their tissues of origin; thus, iPSC-derived cells may be more effective for treatment of myocardial injury if the iPSCs were engineered from cardiac-lineage cells, rather than dermal fibroblasts. Methods and Results— We show that human cardiac iPSCs (hciPSCs) can be generated from cardiac fibroblasts and subsequently differentiated into exceptionally pure (>92%) sheets of cardiomyocytes (CMs). The hciPSCs passed through all the normal stages of differentiation before assuming a CM identity. When using the fibrin gel–enhanced delivery of hciPSC-CM sheets at the site of injury in infarcted mouse hearts, the engraftment rate was 31.91%±5.75% at Day 28 post transplantation. The hciPSC-CM in the sheet also appeared to develop a more mature, structurally aligned phenotype 28 days after transplantation and was associated with significant improvements in cardiac function, vascularity, and reduction in apoptosis. Conclusions— These data strongly support the potential of hciPSC-CM sheet transplantation for the treatment of heart with acute myocardial infarction.